STRATEGI KOMUNIKASI PEMASARAN AKUN INSTAGRAM @AYANAJAKARTA DALAM MENARIK MINAT PENGUNJUNG: Analisis Penerapan Integrated Marketing Communication (IMC) pada Hotel AYANA Midplaza Jakarta melalui Media Sosial Instagram - Erli Suci (Jurnal Kaganga: Jurnal Ilmiah Sosial dan Humaniora, 2026)
This study aims to determine how @ayanajakarta’s communication strategy attracts visitors through Instagram. A communication strategy is a systematic and focused plan for delivering marketing messages to a target audience, with the aim of influencing consumer behavior and achieving predetermined business goals. This research method uses a descriptive qualitative approach, with data collection techniques consisting of in-depth interviews and documentation of @ayanajakarta’s Instagram content uploads. This study employs a constructivist paradigm. The informant selection technique used purposive sampling and Integrated Marketing Communication (IMC) theory. The results show that @ayanajakarta implements a communication strategy based on Integrated Marketing Communication (IMC) theory by implementing eight main IMC elements In an integrated manner: Advertising, Sales Promotion, Events and Experiences, Public Relations and Publicity, Online and Social Media Marketing, Mobile Marketing, Direct and Database Marketing, and Personal Selling. Overall, @ayanajakarta’s communication strategy through Instagram has proven effective in attracting visitors through the use of features such as feed, reels, stories, and explore, as well as consistent visual content management.